Backward Design Implementation in English as a Foreign Language (EFL) Context - Artine Ayu Utami; Barli Bram (Journal of Education and Teaching (JET), 2023)
Backwards design (BD) starts from the desired results or standards and then moved to the evidence of learning obtained from assessment (Tighe & Wiggins, 1999). Despite the conventional trend that designing a curriculum starts by considering the input, a backward design has begun to gain attention as many researchers were interested to study it. This article aims to explore the implementation of backward design in the EFL context. This study applies a qualitative method by analyzing various documents related to the application of backward design in the context of EF with the thematic method of analysis. Several studies were reviewed and analyzed to problematize and make meaning of the implementation of BD in EFL classrooms and its impacts. The backward design can be implemented at various levels ranging from elementary up to university levels. This model can be integrated into the lesson plan, materials development, and classroom instructions and activities. In addition, BD gave a positive impact on students’ motivation, teachers’ professional development, and students’ creative and thinking skills.